Learning transforms functional organization for Mandarin lexical tone discrimination in the brain: Evidence from a MEG experiment on second language learning. (May 2017) - Lee, Rose Ru-Whui; Hsu, Chun-Hsien; Lin, Sheng-Kai; Wu, Denise Hsien; Tzeng, Ovid Jyh-Lang
Abstract: Brain neuroplasticity refers to anatomical changes and functional reorganization in the brain as the results of daily experience and new learning, and thus, should have profound implications for the changes in brain processing during and after bilingual learning. By using a MEG experiment of magnetic mismatch negativity (MMN)/magnetic mismatch field (MMNm) paradigm, the present study examined the brain wave patterns of beginning learners of learning Chinese as a second language (CSL), who enrolled in a short term digital learning program, and were found to have improved sensitivity in discrimination for lexical tones by developing a left lateralized dominance for processing Chinese lexical tones, just like native Mandarin speakers. In the experiment, the measurements of MMNm, with the contrast between large deviant T3/T1 and between small deviant T3/T2, were computed to index the changed patterns of brain processing before and after learning. Results of the MMNm data indicated that activation for large deviant contrast T3/T1 elicited earlier and significantly larger MMN than that of the small deviant contrast T3/T2, which is in line with previous studies done on native Chinese speakers. More importantly, in the comparison of pre-test and post-test time course, the amplitude of MMNm showed a significant increase in the left hemisphere after learning. The evidence indicated clearly a learning effect in the perception of linguistic features and a left lateralized neural network of processing Mandarin lexical tones. Moreover, in the source analysis, the left lateralized patterns of prefrontal generator (i.e., insula) and generator of auditory cortex (i.e., Heschl's Gyrus) changed after learning, which is also consistent with the native Mandarin speaker's response patterns. In sum, the present study provides neural evidence for a functional reorganization in the brains of second language learners, transforming the CSL learners to behave like native speakers in the perception of lexical tones even after just a short-term and non-specific training program. Highlights: A learning effect in perception of linguistic features and a left lateralized neural network of processing lexical tones. Improved sensitivity in discrimination for Mandarin lexical tones after learning, as indexed by MMNm measures. A left lateralization and native-like response pattern for CSL learners after learning, at both sensory and source levels. Duplex processing for phonetic and acoustic features simultaneously and migration of cerebral lateralization. A digital bilingual learning program of short-term and non-specific training for Mandarin lexical tone perception.